Trends in the incidence and survival of cancer in individuals aged 55 years and older in the United States, 1975-2019 - Junpeng Cui; Rongmei Ding; Haifeng Liu; Mingxiu Ma; Ruixue Zuo; Xun Liu (BMC, 2024)
Abstract Background In ageing societies such as the United States, evaluating the incidence and survival rates of cancer in older adults is essential. This study aimed to analyse the incidence and survival rates of cancer in individuals aged 55 years or older in the United States. Methods This retrospective study (1975-2019) was conducted using combined registry data from the Surveillance, Epidemiology, and End Results database. Data from the 9, 12, and 17 Registries (Nov 2021 Sub) datasets were used. Results In 2019, the incidence of cancer in individuals older than 55 years and the overall population was 1322.8 and 382.1 per 100,000 population, respectively. From 2000 to 2019, the incidence of cancer in individuals older than 55 years showed a decreasing trend, whereas their five-year survival rates showed an increasing trend. The incidence of cancer in the 75-79 and 80-84 year age groups was the highest among all age groups. Conclusions The incidence of colon cancer declined significantly, whereas that of intrahepatic bile duct cancer increased considerably. These trends may be due to increased screening for cancers with high incidence rates and improved control of the risk factors for cancer. Rapid development of targeted therapy and immunotherapy combined with early tumour detection may be an important reason for the improved survival rates.